LANGUAGING WHAT I LEARN: INCIDENTAL GRAMMAR LEARNING AND LANGUAGE AWARENESS ON KOREAN-DRAMA VIEWERS - Sya'baningrum Prihhartini; Muhammad Abdillah Harsamuda (Fakultas Komunikasi, Sastra, dan Bahasa, 2023)
The present study investigated incidental grammar learning through movies, specifically for Korean drama viewers. As they get exposed to the Korean language through the dramas/variety shows that they frequently watch, the possibility of them being aware of how Korean language, or Hangul, works seems to be potentially high. The present study applied a mixed-method approach through an open-ended survey which consists of 13 items. Nine items were closed-ended questions while four items were open-ended questions. This study uses a convenience sampling to gather the respondents. The survey was distributed for a week and responded by 36 respondents. The results of the current study show that the majority of the respondents never received formal lessons of Hangul and got exposed to Hangul only through Korean dramas and variety shows. In addition, the respondents show a sort of awareness toward some Hangul morphological forms like plural markers, closeness markers, and a syntactical aspect. The findings show that through Korean drama watching, the Korean drama viewers seem to notice the language pattern of Hangul. The findings suggest that using movies as a learning platform seems to have a positive impact on language learning.